Phytoremediation: A Promising Approach for Revegetation of Heavy Metal-Polluted Land - Yan, An; Wang, Yamin; Tan, Swee Ngin; Mohd Yusof, Mohamed Lokman; Ghosh, Subhadip; Chen, Zhong (Frontiers in Plant Science, 2020)
Heavy metal accumulation in soil has been rapidly increased due to various natural processes and anthropogenic (industrial) activities. As heavy metals are non-biodegradable, they persist in the environment, have potential to enter the food chain through crop plants and eventually may accumulate in human body through biomagnification. Due to their toxic nature, heavy metal contamination has posed a serious threat to human health and the ecosystem. Therefore, remediation of land contamination is of paramount importance. Phytoremediation is an eco-friendly approach that could be a successful mitigation measure to revegetate heavy metal-polluted soil in a cost effective way. To improve the efficiency of phytoremediation, a better understanding of the mechanisms underlying heavy metal accumulation and tolerance in plant is indispensable. In this review, we describe the mechanisms of how heavy metals are taken up, translocated and detoxified in plants. We focus on the strategies applied to improve the efficiency of phytostabilization and phytoextraction, including the application of genetic engineering, microbe-assisted and chelate-assisted approaches.